Fishery of sciaenids off Veraval with special reference to growth, mortality and stock assessment of Otolithes cuvieri (Trewavas, 1974) - Manojkumar, P P (Indian Journal of Fisheries, 2011)
Sciaenids form an important demersal finfish resource off Veraval and contribute about 12 % to the total marine landings. They are exploited mainly by trawls and gillnets with an annual average landing of 9086 t and 323 t respectively during 1986-95. Nearly 16 species contribute to the sciaenid fishery of which, Otolithes cuvieri and Johnius glaucus contributed 52.6% and 13.8 % respectively. In gill net seven species contribute to the landings, dominated by Otolithes cuvieri and Protonibea diacanthus. The peak landing of sciaenids was noticed in September and January. Studies on O. cuvieri revealed that there was no significant difference in the length weight relationship between the sexes, and hence a common regression was fitted as Log W = -4.4632 + 2.9701 Log L (r=0.9036). The asymptotic length (Lô€ƒ) and growth coefficient (K) were estimated as 382 mm and 0.89 y-1 respectively. O. cuvieri grows to 225, 317, 354, 371 and 382 mm at the end of 1st, 2nd, 3 rd, 4th and 5th years. The fishery mainly consisted of 0 and 1 year classes. The average instantaneous rates of total, natural and fishing mortalities were 2.86 y-1, 0.81 y-1 and 2.05 y-1 respectively. The length at first capture was 148 mm at which the age works out to be 0.5 year. The exploitation ratio is higher than the Emax estimated indicating that the resource is overexploited. In view of the heavy fishing pressure, there is a need for reducing the fishing effort to sustain the fishery.